2005
DOI: 10.1080/08109020500085601
|View full text |Cite
|
Sign up to set email alerts
|

Mobile message services and communications policy

Abstract: Something of a design after-thought, mobile phone SMS (Short-Message Services) have been enthusiastically adopted by consumers worldwide, who have created a new text culture. SMS is now being deployed to provide a range of services and transactions, as well as playing a critical role in offering an interactive path for television broadcasting. In this paper we offer a case study of a lucrative, new industry developing internationally at the intersection of telecommunications, broadcasting, and information serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…For this reason, the terms and conditions of consumer protection in these proprietary spaces requires serious attention from government, in order to ensure that the industry does engage in fair trade practices (Goggin and Spurgeon, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the terms and conditions of consumer protection in these proprietary spaces requires serious attention from government, in order to ensure that the industry does engage in fair trade practices (Goggin and Spurgeon, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…As social relations of premium rate services are made opaque by the operation of claims to confidentiality in the market, very little of the information needed to make judgements about the equity and fairness of premium rate services' terms of trade circulates among consumers, and this puts them at a serious, structural disadvantage. For this reason, the terms and conditions of consumer protection in these proprietary spaces requires serious attention from government, in order to ensure that the industry does engage in fair trade practices (Goggin and Spurgeon, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, extant research also shows that regulatory issues including legal barriers have been identified as a major force in the development and deployment of pervasive e-health solutions [24,42]. In fact, because extant policy frameworks that are inherited from specific national and international settings are ''not wellplaced to deal with contemporary communications technologies that blur the boundaries among these'' (page 181 in [17]), pervasive e-health solutions may not always fit within traditional healthcare regulation models [47]. For example, while in some regulatory regimes there may be legal obstacles that influence the reimbursement structures and payments when treatments are carried out in the e-health realm (e.g.…”
Section: Introductionmentioning
confidence: 96%
“…This is a stage that is generally overlooked. That is, answers are needed for potential legal, societal, and general economic concerns that pervasive e-health solutions may introduce [17,39,48].…”
Section: Introductionmentioning
confidence: 99%
“…Morris and Venkatesh (2000) were of the view that "Age has been of significant interest to social psychologists as well as marketers in the past"; these cellular companies are mainly targeting youth for subscription of late night call packages and unlimited SMS. "SMS was built into the European Global System for Mobile (GSM) working as an additional capability (Goggin et al, 2005). Now in many countries SMS perceived as cheap, utilized as one-to-one, or one-to-many, mostly communication is done in leisure time.…”
Section: Introductionmentioning
confidence: 99%